The mermaid in the basement [large type] - Morris, Gilbert (Morris, Gilbert. Lady Trent mysteries, 2009)
It's London, 1857, and everything is at stake for Serafina Trent, a woman of means, but not the typical Victorian lady who feels her place is to be seen and not heard. Wealthy widow of a nobleman and daughter of a famous scientist, she's a skeptic who only trusts what can be proven. When her brother's most recent female dalliance, a beautiful actress, is found murdered, all evidence points to him. Especially since the actress had just rejected him in a most public manner. Now everyone believes Clive is headed for the gallows. Everyone, that is, but Serafina.